2009
DOI: 10.1111/j.1475-6773.2008.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Translating Research into Practice Intervention Improves Management of Acute Pain in Older Hip Fracture Patients

Abstract: The TRIP intervention improved quality of acute pain management of older adults hospitalized with a hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 69 publications
0
53
0
1
Order By: Relevance
“…A number of studies have shown that if effectively implemented, EBPs can improve patient outcomes and reduce the use of resources 17-18. Titler et al18 demonstrated that a Translating Research into Practice (TRIP) intervention, which assisted in implementing EBPs in pain management, had a measureable effect on nurse’s practices in an acute care setting.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that if effectively implemented, EBPs can improve patient outcomes and reduce the use of resources 17-18. Titler et al18 demonstrated that a Translating Research into Practice (TRIP) intervention, which assisted in implementing EBPs in pain management, had a measureable effect on nurse’s practices in an acute care setting.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, patients with the poorest prognosis for survival in the year after fracture also may be at greatest risk for inadequate treatment of pain in the acute setting. Improving the recognition and treatment of acute pain, potentially through use of regional anesthesia [8] or structured care pathways including pain-management protocols [18], represents a key opportunity to improve endof-life care in orthopaedics.…”
Section: Treatment Of Painmentioning
confidence: 99%
“…23,31,32 Titler et al 23 utilized the model when developing strategies aimed at promoting EBP for management of acute hip pain in older patients with hip fracture. During the planning phase, each of the areas within the TRIP model was used to develop implementation strategies.…”
Section: Examples From Other Health-care Professionsmentioning
confidence: 99%
“…29 This model was selected as it has been shown to positively influence adoption of EBP when tested in other clinical environments. 23,[30][31][32] The model serves as a framework for developing strategies that promote implementation of EBP. It assumes that adoption of research is influenced by the characteristics of the EBP topic (type and strength of evidence; clinical relevance) and the manner in which it is communicated to users in a social system.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation